HUBUNGAN TINGKAT STRES DENGAN DURASI PENGGUNAAN TIKTOK PADA REMAJA DI DUSUN JAGUL DESA SENDANGREJO KECAMATAN LAMONGAN - Syafiq Azziyad, Muhammad; Maulana Kahfi; Moh. Saifudin; Siti Sholikhah (PT Wahana Global Education, 2025)
Adolescence is a transition period in the human life span that connects childhood and adulthood. According to the World Health Organization (WHO), a teenager is someone who is in a transitional stage between childhood and adulthood, with an age limit of 12 to 24 years. Constant stress can also affect mental health problems such as depression, anxiety, dropping out of school, and even suicide. Social media (Tiktok) is able to provide positive reactions in individuals, one of the many ways that is used for coping is playing TikTok. The aim of this research is to analyze the relationship between stress levels and duration of TikTok use among teenagers in Jagul Hamlet, Sendangrejo Village, Lamongan District. This research design was a crosssectional method, a sample of 53 teenagers was obtained using a total sampling technique. The instrument in this research is a questionnaire, data analysis using the Spearmen rho test. The research results showed that most teenagers used TikTok for a short duration, 32